2012
DOI: 10.1111/j.1744-7402.2012.02801.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Cleaning and Antibacteric Ceramic Tile Surface

Abstract: The aim of this investigation was the surface functionalization of industrial ceramic tiles by sol‐gel technique to improve at the same time the cleanability and the antibacterial activity of surfaces. This objective was pursued through the design and preparation of nanostructured titania‐silver coating that was deposited on glazed, unglazed, and polished tiles by air‐brushing. The obtained results showed that the applied coatings are transparent, show a good adhesion, and a remarkable antibacterial activity u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 22 publications
0
38
2
1
Order By: Relevance
“…This also agrees with earlier observations by Liu et al [50] and Gogniat et al [38], which showed a loss of bacterial culturability after contact with TiO 2 nanoparticles in the dark. A study by de Niederhãusen and Bondi [51] on the self-cleaning of Ag-TiO 2 -coated ceramic tiles also showed significant antibacterial activity for 24 h in the dark.…”
Section: Stirring Experimentsmentioning
confidence: 99%
“…This also agrees with earlier observations by Liu et al [50] and Gogniat et al [38], which showed a loss of bacterial culturability after contact with TiO 2 nanoparticles in the dark. A study by de Niederhãusen and Bondi [51] on the self-cleaning of Ag-TiO 2 -coated ceramic tiles also showed significant antibacterial activity for 24 h in the dark.…”
Section: Stirring Experimentsmentioning
confidence: 99%
“…Antimicrobial products can be formulated using biocides [21], metal oxide nanoparticles [22][23][24] or bio-based products [25]. A substantial amount of literature has been published on the effect of photocatalytic TiO 2 nanoparticles on microorganisms [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…To confer self-cleaning properties to ceramic tiles, TiO 2 has been deposited as thin films on their surface [13][14][15]. Among the different methods used to prepare TiO 2 films [16][17][18][19], the sol-gel process is considered as one of the most promising alternatives because it presents a number of advantages, such as low sintering temperature, versatility of processing, and good homogeneity at low cost [12,15].…”
Section: Introductionmentioning
confidence: 99%